2013
DOI: 10.1007/s00464-013-3073-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of old age on surgical outcomes of totally laparoscopic gastrectomy for gastric cancer

Abstract: The results of this study demonstrated that old age can have an effect on the surgical outcomes of totally laparoscopic gastrectomy. This study especially showed that elderly patients are affected by the return of bowel movement after totally laparoscopic gastrectomy. On the other hand, however, it is presumed that old age has not had a serious impact on surgical outcomes in totally laparoscopic gastrectomy because no difference in the severe postoperative complication rate was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 50 publications
1
21
0
1
Order By: Relevance
“…Reasons may be statistically significant younger age and less comorbidity in the RADG group. Younger people recover well and faster in general, which is mostly related to less postoperative complications [21][22][23][24][25]. That could be a more tentative factor than surgical method when we think our previous report that surgical stress-wise robot does not have any benefit [1].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons may be statistically significant younger age and less comorbidity in the RADG group. Younger people recover well and faster in general, which is mostly related to less postoperative complications [21][22][23][24][25]. That could be a more tentative factor than surgical method when we think our previous report that surgical stress-wise robot does not have any benefit [1].…”
Section: Discussionmentioning
confidence: 99%
“…26 Based on these reasons, some authors have suggested that limited surgery should be considered for this patient population to reduce operative mortality. 8,27,28 To date, many studies have demonstrated the benefits of laparoscopic gastrectomy, which include an improved cosmetic effect, less pain, quicker recovery, shorter hospital stay, and better quality of life. 29,30 When considering the trauma induced by surgery, laparoscopic surgery may be optimal for minimizing surgical trauma in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown acceptable outcomes in terms of morbidity and mortality in patients older than 70 years of age undergoing gastrectomy for gastric cancer [19], pancreatectomy for pancreatic cancer [20], or liver metastasectomies [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies in the past have evaluated the safety, effectiveness, and feasibility of other major abdominal operations in the elderly, such as liver, pancreatic, gastric, and ovarian cancer surgery, showing a low mortality and acceptable morbidity with a careful patient selection process [1922]. …”
Section: Discussionmentioning
confidence: 99%